KEADILAN HUKUM PADA PERTIMBANGAN HAKIM DALAM MEMUTUS HAK ASUH ANAK - Umar Haris Sanjaya (Universitas Airlangga, 2015)
This reseach is focused on the making argument to looking justice progress of verdict. The justice progress which is mean is justice on the law of procedure. Law of justice is need to implemented by judge into the case as well as regulated in the Act. This research using context of problems as how the judges giving arguments of law into his verdict on the case of children custody and will continue with review it those verdict as well as law and justice consideration. Research result found three judges verdicts which are related with children custody on 2010. Those verdicts give a one of legal basic for three different consideration of verdict. 1st children custody give under mother, 2nd children custody give under father, 3rd children custody give to parents, its becaus of each party did not request specifically for children custody. For the conclusion overall judges use the law logic in the term of correct as well as legal basis. Its comply all of justice value to making verdict. Thus the justice which apply by judges is procedure justice eventhough those different in decision making.